Silviculture, Genetics and Molecular Breeding of Neolamarchia cadamba (Kelampayan) in Sarawak - Ho, Wei Seng; Ling, Kwong Hung; Pang, Shek Ling (UNIMAS Publisher, 2020)
Neolamarckia cadamba (Roxb.) Bosser or locally known as Kelampayan in Sarawak is a large deciduous tree with broad umbrella-shaped crown and straight cylindrical bole. It has been known as a miracle tree by many researchers since 1960s, partly because of its fast-growing characteristic and its medicinal value in the traditional systems of medicine. It is considered as one of the promising indigenous plantation tree species in Sarawak. The demand for high-quality planting materials of Kelampayan is drastically increased over the years. Concurrently, extensive studies have been carried out to bridge the gap in demand and supply of high-quality Kelampayanseedlings for planted forest development in Sarawak. These studies include silvicultural management practices, genetic diversity, molecular breeding and tissue culture ofKelampayan. Besides emerging technologies such as high-throughput next-generation sequencing (NGS) and genotyping technologies in identifying marker-trait association or association mapping in Kelampayan are also discussed in this publication. These technologies should be perceived as the new tools to complement conventional techniques in solving the limitations of tree improvement due to the long generation intervals of trees, and therefore resulting in a better economic return in the production of high-quality planting materials due to the reduction of cost and time. This book will be an essential reference for researchers and tree breeders to understand better the biology of Kelampayan that leads to the more efficient management of breeding stocks and genetic improvement of Kelampayan, especially on the production of elite Kelampayan clones. It will also serve as a useful reference for plantation managers and investors, primarily in the decision-making process for the development of large-scale Kelampayan planted forests.